2005
DOI: 10.1111/j.1601-0825.2005.01087.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ninhydrin method of detecting amine compounds with other methods of halitosis detection

Abstract: The salivary amine levels significantly correlated with VSC levels and organoleptic scores. Therefore, the ninhydrin method of detecting salivary amines may be an alternative or additional method of diagnosing halitosis. This method may also be used to evaluate treatment efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 8 publications
2
17
0
4
Order By: Relevance
“…In agreement with previous reports (Iwanicka‐Grzegorek et al. ), all the parameters used to assess the level of amines in saliva in this study, showed significant differences between patients with and without oral malodour. Also the difference in the level of sulphur compounds in patients with or without oral malodour is well documented (Tonzetich , Rosenberg et al.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous reports (Iwanicka‐Grzegorek et al. ), all the parameters used to assess the level of amines in saliva in this study, showed significant differences between patients with and without oral malodour. Also the difference in the level of sulphur compounds in patients with or without oral malodour is well documented (Tonzetich , Rosenberg et al.…”
Section: Discussionsupporting
confidence: 93%
“…Salivary amine levels measured by the ninhydrin method significantly correlated with organoleptic scores (r = 0.60; p 0.001) and sulphide monitor measurements (r = 0.54; p 0.001) in halitosis patients and control subjects. 114 …”
Section: Ninhydrin Methodsmentioning
confidence: 97%
“…The results of ninhydrin methods show a significant correlation with organoleptic scores and sulfide monitor measurements. [101]…”
Section: Assessment Of Halitosismentioning
confidence: 99%